Criminal Threats Against Personnel Control Of Land Without Rights - Arif Nurcahyono; Amin Purnawan (Law Development Journal, 2020)
The objectives of this research are 1) to find out and explain what is meant by the criminal act of control of land without a power permit or entitled and its elements, 2) Know and explain whether or not the criminal threat is relevant to the perpetrator in accordance with current developments. The results of this study concluded that: 1) Article 6 paragraph (1) letter a of the PRP Act No. 51 of 1960. The criminal act of using land without a permit with the right or legal proxy in the Criminal Code basically contains the following elements: as stellionate. b) It is known that there are other persons entitled to the land; The crime in this article is called Stellionate crime, which means "embezzlement of rights over immovable property", c) Failure to inform others that the land has been used as land for debt or has been mortgaged. 2) Factors Occurring Criminal Actions of Land Tenure Without Rights (a) Internal Factors 1) Educational Factors, 2) Individual Factors, (b) External Factors 1) Economic Factors 2) Environmental Factors, 3) Law Enforcement Factors, 4) Global Development Factors (Technology). 3) Based on the Supreme Court Decision Number 73 / Pid / 2015 / PT SMG has fulfilled the elements of error, the ability to be responsible, there is no excuse for forgiveness, against the law, and the manifestation of behavior and actions of subjective elements in error in practice is only aimed at everyone (whoever ) Article 6 paragraph (1) Act No. 51 Prp Of 1960 and no criminal threat against a legal entity or a corporation is regulated.